Association of Body Weight Change and Fluid Balance With Extubation Failure in Intensive Care Unit Patients: A Single-Center Observational Study. (February 2021) - Maezawa, Shota; Kudo, Daisuke; Miyagawa, Noriko; Yamanouchi, Satoshi; Kushimoto, Shigeki
Purpose: To elucidate whether fluid balance and body weight change are associated with failed planned extubation. Materials and Methods: Patients who received invasive mechanical ventilation for over 24 hours were enrolled and divided into extubation success and extubation failure groups. Fluid balance and body weight fluctuation within 24 and 48 hours before extubation and from admission to planned extubation were calculated. The primary outcome was extubation failure (ie, all-cause reintubation within 72 hours). The association of extubation failure with fluid balance and body weight change was assessed via logistic regression analysis. Results: Extubation failure occurred in 12(7.4%)/161 patients. The extubation success group had a significantly lower fluid balance within 24 hours before extubation than did the extubation failure group (−276 mL [−1111 to 456] vs 1217 mL [503 to 1875], P = .002). However, fluid balance within 48 hours before extubation, cumulative fluid balance, and body weight change were not significantly different between the 2 groups. The sensitivity and specificity of water balance +1000 mL within 24 hours before extubation for the extubation failure group were 0.54 and 0.84, respectively, based on the receiver operating characteristic curve. Logistic regression analysis showed that fluid balance within 24 hours before extubation was associated with extubation failure (odds ratio: 22.9, 95% confidence interval: 4.1-128.4). Conclusions: A larger fluid balance within 24 hours before extubation is associated with extubation failure. Thus, fluid balance may be a good indicator of extubation outcome.